EFEKTIVITAS MANAJEMEN BERBASIS MADRASAH DI MI DARUSSALAM WANUTENGAH KECAMATAN PARAKAN KABUPATEN TEMANGGUNG - Faizah Faizah; Ahmat Yuliyanto; Effi Wahyuningsih (As-Sibyan, 2022)
This study aims to determine the effectiveness of Madrasah-Based Management Implementation at MI Darussalam Wanutengah, Parakan District, Temanggung Regency. This research is included in the descriptive qualitative research. The data collection technique used is the method of observation, interviews, and documentation. The data analysis technique used in this study is qualitative analysis through data reduction, data presentation, and data inference. Based on the results of the research that has been carried out, it can be concluded that (1) the concept of Madrasah-Based Management is understood by the stakeholders of MI Darussalam Wanutengah as a madrasa management model that provides autonomy and flexibility to madrasas and encourage the participation of madrasa residents and the community to improve the quality of education. The aim is to improve the performance of madrasas which include improving the quality, effectiveness, efficiency, productivity and innovation of education based on the principles of good governance towards the realization of effective madrasas. (2) The implementation of Madrasah-Based Management at MI Darussalam Wanu was going well, covering 9 aspects, namely: Planning and evaluation; Curriculum management; Management of teaching and learning process; Manpower management; Facility management; Financial management; Student services; School-community relations; and Madrasah climate management. (3) The supporting and inhibiting factors for the implementation of Madrasah-Based Management at MI Darussalam Wanutengah come from internal factors and external factors.